Shear-band structure and chemistry in a Zr-based metallic glass probed with nano-beam x-ray fluorescence and transmission electron microscopy. (August 2019) - Liu, C.; Cai, Z.; Xia, X.; Roddatis, V.; Yuan, R.; Zuo, J.M.; Maaß, R.
Abstract: An apparent local change in chemistry in shear-bands can be observed in a Zr-based metallic glass using correlative x-ray fluorescence and electron spectroscopy. Further analysis suggests that this finding is due to the local volumetric change of the shear-band structure. These results emphasize the importance of correlated analytical methods to unambiguously reveal structural and chemical changes caused by strain localization in metallic glasses. Graphical abstract: Unlabelled Image